Orbital Parameters of 665 Double-lined Spectroscopic Binaries in the LAMOST Medium-resolution Survey - Sufen Guo; Mikhail Kovalev; Jiao Li; Guoliang Lü; Shi Jia; Zhenwei Li; Jiangdan Li; Jianping Xiong; Mingkuan Yang; Tongyu He; Xuefei Chen; Zhanwen Han (The Astrophysical Journal Supplement Series)
The period, mass ratio, eccentricity, and other orbital parameters are fundamental for investigating binary star evolution. However, the number of binaries with known orbital parameters remains limited. Utilizing the LAMOST medium-resolution spectroscopic survey, we derived orbital solutions for 665 SB 2 binaries by fitting the radial velocities of 1119 SB 2 systems with at least six observations, employing a modified version of The Joker optimized for SB 2 binaries. To ensure the reliability of the results, four selection criteria were applied: reduced chi-square, normalized mean absolute error, maximum phase gap, and radial velocity distribution metric. After applying these criteria, 665 reliable orbits were retained. Comparison with Kepler, TESS, and Zwicky Transient Facility light-curve data shows excellent agreement, with discrepancies in some cases attributed to shorter pulsation periods observed in light curves. Additionally, good consistency is found between our periods and those of SB 1 systems in Gaia data. These orbital solutions contribute to understanding binary star evolution and the statistical properties of binary populations.